Body Mass Index and stimulus control: Results from a real-world study of eating behaviour. (1st November 2020) - Franja, Stefania; Elliston, Katherine G.; Ferguson, Stuart G.
Abstract: Background: Evidence suggests decisions about when, what, and how much to eat can be influenced by external (location, food outlet presence, food availability) and internal (affect) cues. Although the relationship between stimulus control and obesity is debated, it is suggested that individuals with higher BMIs are more driven by cues to eating than individuals in the healthy-weight range (HWR). This study investigates the influence of stimulus control on real-world food intake, and whether stimulus control differs by BMI. It was hypothesised that, compared to those in the HWR, eating among individuals with higher BMIs would be under greater stimulus control. Method: 74 participants ( n  = 34 BMI < 24.9, n  = 40 BMI > 24.9) recorded food intake for 14 days using Ecological Momentary Assessment. Participants also responded to 4–5 randomly-timed assessments per day. Known external and internal eating cues were assessed during both assessment types. Within-person logistic regression analyses were used to predict eating vs. non-eating occasions from stimulus control domains. Findings: Results support the hypothesis that eating was influenced by stimulus control: food availability, affect, time of day, and location significantly distinguished between eating and non-eating instances (AUC-ROC = 0.56-0.69, all p 's < 0.001). The presence of food outlets was significantly better at distinguishing between eating and non-eating instances for those with higher BMIs (compared to individuals in the HWR). Discussion: Results support the notion of stimulus control in shaping eating decisions. Differences in levels of stimulus control between participants in the HWR compared to those with a high BMI suggest that dietary improvement interventions may be more effective when they are tailored to the individual and consider environmental influences on eating behaviour.